Spatial Transcriptomics‐Based Identification of Molecular Markers for Nanomedicine Distribution in Tumor Tissue. Issue 11 (30th September 2022) - Park, Jeongbin; Choi, Jinyeong; Lee, Jae Eun; Choi, Hongyoon; Im, Hyung‐Jun
Abstract: The intratumoral accumulation of nanomedicine has been considered a passive process, referred to as the enhanced permeability and retention effect. Recent studies have suggested that the tumor uptake of nanomedicines follows an energy‐dependent pathway rather than being a passive process. Herein, to explore the factor candidates that are associated with nanomedicine tumor uptake, a molecular marker identification platform is developed by integrating microscopic fluorescence images of a nanomedicine distribution with spatial transcriptomics information. When this approach is applied to PEGylated liposomes, molecular markers related to hypoxia, glycolysis, and apoptosis can be identified as being related to the intratumoral distribution of the nanomedicine. It is expected that the method can be applied to explain the distribution of a wide range of nanomedicines and that the data obtained from this analysis can enhance the precise utilization of nanomedicines. Abstract : The intratumoral accumulation of nanomedicine is considered a passive process, referred to as the enhanced permeability and retention effect, which is now challenged. Herein, to explore the factor candidates that are associated with nanomedicine tumor uptake, a molecular marker identification platform is developed by integrating microscopic fluorescence images of a nanomedicine distribution with spatial transcriptomics information.